Penyelesaian sengketa letter of credit ekspor-impor syariah pascaputusan Mahkamah Konstitusi Nomor 93/PUU-X/2012 - Titik Triwulan Tutik (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
This research is aimed to examine on the dispute settlement Letter of Credit (L/C) Import-Export in sharia banking. This dogmatic study was supported by the statute and conceptual approach. The steps of research were conducted by collecting the primary and secondary data. All of the data were noted using card system based on the subjects of the research problem and writing system. The results of the research show that: First, the position of the Letter of Credit as cross-border transactions in the Sharia banking, not only just set in national contract law, but also stipulated in the International treaty provisions do not contrast with the principles of Sharia. Secondly, in the event of dispute resolution issues of Islamic banks, according to Constitutional Court Decision No. 93/PUU-X/2012 can use two (2) that litigation and non-litigation. A litigation path into the absolute authority of religious courts, while the path of non-litigation the parties can make a choice no explanation as specified in Article 55 paragraph (2) of Law Number 21 Year 2008 concerning Sharia Banking but can also take other alternatives in accordance with a contract that banks have agreed.